The The Process of Deepening the Character in Dokudrama “Film Perjuangan K.H. Muhyiddin” - Faiz Bolkiah (JOMANTARA, 2021)
Dokudrama is a non-fiction film that presents a story based on a true story. Besides being an entertainment medium, a film can also be a learning medium since film provides a good story content and messages. Therefore, it needs an actor as a subject to convey the message of the story that the director wants to deliver. To play a character in a movie, an actor must be able to delve into whatever character is given. Unlike documentaries, dokudrama films use actors as the main subject. An actor in a docudrama should be able to play a subject who has ever been real. An actor in a dokudrama film should be able to play a good role without removing the hallmarks of the original subject. A deepening process in a role, making every actor have their own way in learning the character. The differences in studying and delving into these characters is the focus of this research by using qualitative research methods, by re-describing the results of the researcher's analysis with the main theory. To create this study, the researchers used the presentation theory from Stanislavsky. The acting theory of this presentation has been used since the world of casting art entered Indonesia. This research aim is to find out the character deepening conducted by actors in the dokudrama film “Perjuangan K.H. Muhyiddin” based on the Stanislavsky’s acting presentation theory. Keywords: Dokudrama, Qualitative, Casting, Stanislavsky, Biography